Spontaneous Intracerebral Haematoma-II:Post-Operative Changes and Outcome of Burrhole Aspiration after Urokinase Mediated Clot Lysis - Hossain, Mohammad Nazrul; Nabi, Shahryar; Hossain, Sk Sader (Journal of Bangladesh College of Physicians and Surgeons, 2017)
Background: Treatments of intracerebral hematoma (ICH) are controversial and surgical interventions in spontaneous ICH are required and more accepted. Although advantage of neurosurgical intervention conservative treatment of ICH has not been established, recent reports have suggested favourable effects of blood clot removal after liquefaction by means of urokinase. Objectives: To study the intervention by and out come in without or with complications of Burrhole aspiration treatment after urokinase mediated clot lysis; Study Design : Prospective interventional study. Place and Duration of Study: Departments of Neurosurgery and Radiology & Imaging ,Dhaka Medical College Hospital, Dhaka, Bangladesh from July 2010 to December 2010; Materials &Methods: A total of 30 Bangladeshi patients with spontaneous ICH (Age range: 40-75yrs,Mean age ±SD:59.1±11.52 years, Gender : 22 males, 8 females) full filling the criteria for spontaneous ICH were included in the study. The desired information relevant to the objectives were obtained and recorded carefully using a structured questionnaire; The Patients were treated with Burrhole aspiration after urokinase mediated lysis , evaluated for out come , complications and death and statistically analyzed ; Results: The results on delays of intervention ,types of intervention, doses of urokinase, post-operative changes in haematoma volume, outcome with Glasgow outcome scale(GOS) and GOS at followup, complications and death were presented with statistical analyses and significance .The outcome and death were compared with various variables such as hypertension (p <0.05), diabetes mellitus (p< 0.05) primary GOS (P<0.05),site of hematoma (p<0.05),volume of haematoma (p<0.05),ventricular extension of hematoma (p<0.05) and delay from ictus to intervention (p<0.05). Conclusion : It was observed that early treatment (within 24 hours of occurance) by using minimally invasive technique and clot removal by urokinase mediated lysis can improve the consequences especially those with haematoma volume < 40 ml, lobar haematoma and without ventricular extension. Bad prognostic factors were increase of blood pressure, diabetes mellitus, GOS level <8, haematoma in the basal ganglia , ventricular extension of the haematoma volume> 40 ml and delay in intervention. However, the present was conducted with 30 patients only and therefore, studies with larger number of patients are required to draw more meticulous and more definitive conclusions. J Bangladesh Coll Phys Surg 2016; 34(2): 64-75